How Can Eastern/Southern Mediterranean Countries Resolve Quality and Safety Issues in Transfusion Medicine? - Haddad, Antoine; Bou Assi, Tarek; Garraud, Olivier (Frontiers in Medicine, 2018)
Unlike their Western counterparts, some of the Eastern/Southern Mediterranean countries lack centralized coordinated blood transfusion services leading to an unequal blood safety level. This was recently highlighted by a recent WHO regional committee report in which WHO urges these countries to establish and implement a national blood system with well-coordinated blood transfusion activities and to make attempts to reach 100% Voluntary non-remunerated blood donation. The objective is thus to meet the same levels or standards as Western countries in term of self-sufficiency and blood safety. This raises the question whether these countries can either comply with Western countries’ guidelines and experiences, or develop their own safety scheme based on proper socio-political and economic features. Another option is to identify efficient and cost-effective strategies set up successfully in neighbor countries sharing cultural and economic features. To address this issue—and make an attempt to achieve this goal—, we designed a number of surveys specifically addressed to Mediterranean countries, that were sent out to the national authorities; so far, five surveys aim at covering all aspects in blood collection, processing, testing, inventory and distribution, as well as patient immune-hematological testing and follow up (including surveillance and vigilances). It is anticipated that such practice can help identifying and then sharing the more successful and cost-effective experiences, and be really focused on Mediterranean areas while not necessarily copying and pasting experiences designed for Western/Northern areas with significantly distinct situations.